The determinants of securities trading activity: Evidence from four European equity markets - Silvio John Camilleri; Francelle Galea (Journal of Capital Markets Studies (JCMS), 2019)
Purpose - The purpose of this paper is to obtain new empirical evidence about the connections between equity trading activity and five possible liquidity determinants: market capitalisation, dividend yield, earnings yield, company growth and the distinction between recently listed firms as opposed to more established ones. Design/methodology/approach - The authors use a sample of 172 stocks from four European markets and estimate models using the entire sample data and different sub-samples to check the relative importance of the above determinants. The authors also conduct a factor analysis to re-classify the variables into a more succinct framework. Findings - The evidence suggests that market capitalisation is the most important trading activity determinant, and the number of years listed ranks thereafter. Research limitations/implications - The positive relation between trading activity and market capitalisation is in line with prior literature, while the findings relating to the other determinants offer further empirical evidence which is a worthy addition in view of the contradictory results in prior research. - Practical implications This study is of relevance to practitioners who would like to understand the cross-sectional variation in stock liquidity at a more detailed level. Originality/value - The originality of the paper rests on two important grounds: the authors focus on trading turnover rather than on other liquidity proxies, since the former is accepted as an important determinant of the liquidity-generation process, and the authors adopt a rigorous approach towards checking the robustness of the results by considering various sub-sample configurations.
Keywords: 330; Dividend yield; European equity markets; Factor analysis; Liquidity; Liquidity determinants; Market capitalisation; Newly established firms; Securities markets; Trading activity